Public advocacy for the Swedish forest-based bioeconomy - Andtbacka, Hanna (2020)
During the last decade bioeconomy has been presented as a possible solution to the decoupling of the economy’s dependence on fossil fuels. In a Swedish context, the forest sector has emerged as a significant arena of interest and the industry has been defined as a driving agent in the transition. In the light of this, efforts have been made to market the Swedish forest as an attractive resource in order to gain the attention of the public. The purpose of this study is to examine how the dominant forest actors strategically communicate the bioeconomy through the Swedish Forest initiative. Using a social constructionist perspective and a diverse set of concepts streaming from discourse analysis, semiotics and rhetoric the campaigns of the initiative could be explored. The results show that the dominant forest actors formulate a story that portrays the forest as a climate solution and further enforces production interest while neglecting environmental aspects. Additionally, the industry positions itself as essential in a transition towards a forest-based bioeconomy, while marginalizing actors with competing interests such as ENGOs and indigenous Sámi people.